Efficacy and mortality of ceftazidime/avibactam-based regimens in carbapenem-resistant Gram-negative bacteria infections: A retrospective multicenter observational study - Hai-Hui Zhuang; Ying Chen; Qin Hu; Wen-Ming Long; Xiao-Li Wu; Qin Wang; Tian-Tian Xu; Qiang Qu; Yi-Ping Liu; Yi-Wen Xiao; Jian Qu (Elsevier, 2023)
Objectives: Limited data on clinical and microbiological efficacy, patient mortality, and other associated factors are available for ceftazidime/avibactam (CAZ/AVI)-based regimens for carbapenem-resistant Gram-negative bacteria (CR-GNB). This study aimed to assess these issues retrospectively using multicenter data. Methods: This multicenter study included CR-GNB infected patients treated with CAZ/AVI-based regimens for more than three days. Patient characteristics, bacterial culture reports, drug-sensitivity test results, and antibiotic use, including CAZ/AVI use, were extracted from the patient's clinical records. The clinical and microbiological efficacy of the combined drug regimen and patient mortality were evaluated according to corresponding definitions. Univariate and multivariate logistic regressions were performed to explore the efficacy and mortality-related factors. Results: A total of 183 patients with CR-GNB infection were considered for the analysis according to the inclusion and exclusion criteria. After the treatment of CAZ/AVI-based regimens, the clinical efficacy was 75.4 %. The 7-day microbial efficacy and clearance rate after treatment were 43.7 % and 66.0 %, respectively. Moreover, 30-day all-cause and in-hospital mortality were 11.5 % and 14.2 %, respectively. Harboring renal dysfunction (creatinine clearance rate (CCR) of<20 mL/min), cardiovascular diseases, and digestive system diseases were independent risk factors for poor clinical efficacy of CAZ/AVI-based regimens. Bloodstream infection (BSI), patients with the adjusted doses of CAZ/AVI, and CAZ/AVI co-administration with carbapenem were independently associated factors of bacterial clearance by CAZ/AVI-based regimens. Age, total hospital stays, use of mechanical ventilation, and cumulative CAZ/AVI dose were independent factors associated with all-cause mortality. Conclusion: CAZ/AVI was an effective drug in treating CR-GNB infection. CAZ/AVI that is mostly excreted by the kidney and is accumulated in renal impairment should be renally adjusted. Renal dysfunction and the adjusted dose of CAZ/AVI were associated with efficacy. Clinicians should individualize CAZ/AVI regimen and dose by the level of renal function to achieve optimal efficacy and survival. The efficacy of CAZ/AVI in the treatment of CR-GNB infection, as well as the implementation of individualized precision drug administration of CAZ/AVI according to patients' different infection sites, renal function, bacterial types, bacterial resistance mechanisms, blood concentration monitoring and other conditions need to be further studied in multicenter.